Combining a distributed flow manifold and 3D woven metallic lattices to enhance fluidic and thermal properties for heat transfer applications. (May 2017) - Zhao, Longyu; Ryan, Stephen M.; Lin, Sen; Xue, Ju; Ha, Seunghyun; Igusa, Takeru; Sharp, Keith W.; Guest, James K.; Hemker, Kevin J.; Weihs, Timothy P.
Highlights: Propose and design novel flow manifold that is combined with 3D woven lattices. Characterization of pressure drop, average temperature and temperature uniformity. Much superior thermal performance with 3D woven lattices than open spaces. Comparison of the new distributive flow pattern with axial and bifurcated flow cases. Trends between experiments and simulations are in good agreement. Abstract: The fluidic and heat transfer capabilities of 3D woven lattice materials were reported recently under axial and bifurcated flow patterns, but three critical performance indices – pressure drop, average surface temperature and temperature uniformity – could not be optimized simultaneously using these flow patterns. Here we combine the 3D weaves with manifolds to create a novel 3D flow pattern that enhances temperature uniformity, while also maintaining low pressure drops and surface temperatures. These three properties were characterized at room temperature for a range of flow rates using water as the working fluid. Three different weaves thicknesses were investigated: 12.7 mm, 6.4 mm, and 3.2 mm, with manifold thicknesses of 12.7 mm, 19.0 mm, and 22.2 mm, respectively, to provide a constant, combined weave-manifold thickness of 25.4 mm. The properties of this new weave/manifold system are compared to those obtained using just the manifold (with no weave) and just the weave (with no manifold). Comparisons show that the addition of the weave lowers the average substrate temperature and temperature variations significantly, although pressure drop is increased. They also show that the addition of the manifold improves temperature uniformity significantly, and also lowers the average substrate temperature and the pressure drop. No specific ratio of weave to manifold thickness was found to be superior in all of the performance indices. The thermal performances are then evaluated at different pumping powers: the weave/manifold system and its distributed array flow pattern prevail. Finite element simulations were performed on a reduced and simplified model to explain the observed experimental trends, and manifold opening patterns were manipulated to demonstrate further potential property enhancements. The multiple benefits of this manifold system can be extended to common heat exchanger media beyond weaves.